Snapdragons: new blue shoes - Spencely, Louise; Williamson, Melanie (Oxford University Press Oxford, 2004)
Ella's favourite colour is blue, so when she finds her favourite blue shoes are goo small, Grandpa takes her shopping for new ones. Each shop has lots of shoes -- but can Ella find the blue ones she wants?